Assessment on the ecological health of Sepang Besar River, Selangor using Geloina expansa as a biomonitor - Ahmad Wakid, Sarini; Abd Aziz, Nor Azwady; Mustafa, Muskhazli; Syazwan, Wan Mohd; Zulkifli, Syaizwan Zahmir; Alias, Zazali (Malaysian Nature Society, 2023)
Bivalves have been utilised extensively as a biomonitoring agent for heavy metal pollution in the marine ecosystem. In the present study, heavy metal concentrations [e.g., copper (Cu), zinc (Zn), cadmium (Cd), and lead (Pb)] were determined in the soft tissues of bivalve Geloina expansa as well as sediment and water samples collected from the Sepang Besar River on the west coast of Peninsular Malaysia. Bioaccumulation factors, such as biota sediment accumulation factor (BSAF) and biota concentration factor (BCF), were used to estimate metal accumulation. The bivalve tissues were digested and analysed using an inductively coupled plasma optical emission spectrometer (ICP-OES). In sediment samples, the heavy metal concentration was Zn (67 mg/kg) > Cu (23 mg/kg) > Pb) (14 mg/kg), on a dry weight basis. Whereas in water samples, Zn (19.2 g/L) > Cu (1.9 g/L) > Pb (1.0 g/L). Meanwhile, the tissues of G. expansa accumulated heavy metals from the surroundings, with concentrations of Zn (56.63 mg/kg) > Cu (4.10 mg/kg), on dry weight basis. Cd was not detected in the samples. The findings of this study suggested that G. expansa serve as a macroconcentrator (BSAF > 2) for Zn, a deconcentrator (BSAF < 1) for Cu, and a bioaccumulator’ (BCF < 5000) of Zn and Cu.